Diagnostic and therapeutical approaches to H3K27M-altered diffuse midline glioma in children: a review - D. A. Morgacheva; D. A. Sitovskaia; Yu. V. Dinikina (Онкогематология, 2023)
H3K27M-altered diffuse midline gliomas are the most devastating pediatric brain tumors. These tumors are characterized by lesion of central nervous system midline structures, diffuse infiltrative growth and fatal prognosis. The pathogenesis of H3K27M-altered diffuse midline glioma is based on unique epigenetic and genetic changes which are associated with histone 3 (H3) alterations. Clinical disease course usually is non-specific, that could hamper diagnosis establishment and defines high prevalence of disseminated tumor stages. Diagnostic approach includes neuroimaging, various laboratory and molecular methods, including high throughput sequencing, which allows finding potential targets for precise therapy. Despite the availability of anti-tumor technologies, including targeted therapy and immunotherapy, the standard of care for H3K27M-altered diffuse midline glioma is radiation therapy, which does not allow achieving long-term event-free survival. A dismal prognosis and absence of curative options for these tumors determine the necessity of new treatment methods search that could improve patients’ outcome. In this article we present current worldwide data of the diagnosis and treatment trends in H3K27M-altered diffuse midline glioma.